Sistem Pendukung Keputusan Penentuan Kelayakan Kandang Ayam Broiler Menggunakan Metode Analytic Hierarchy Process-Weighted Product (AHP-WP) [Studi Kasus PT. Semesta Mitra Sejahtera Wilayah Jombang, Kediri, dan Tulungagung] - Ichwanda Hamdhani; Nurul Hidayat; Imam Cholissodin (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The rapid development of chicken meat affects the performance of chicken farmers, especially broiler chickens. In order to produce a quality broiler chicken, one of the factors that influence it is the feasibility of the chicken coop. Of these problems, it takes an application that is capable of processing data to make a decision support system that is useful in giving the right decision about the eligibility of broiler chicken coop. The AHP-WP method was chosen because it was able to select the best alternative from a number of alternatives. Testing of the method used is to make changes to paired matrix comparison to get the priority weighting criteria. The lowest matching result on the 1st matrix with the value Î»_max = 7.457649, the value of CI = 0.076275, the value of CR = 0.057784 produces a match rate of 69%. Meanwhile, the highest match rate in the 6th matrix with the value of Î»_max = 7.769787, the value of CI = 0.128299, the value of CR = 0.097197 produces a match rate of 94%.